Switching Between LC-ESI-MS/MS and EMIT Methods for Routine TDM of Valproic Acid in Pediatric Patients With Epilepsy: What Clinicians and Researchers Need to Know - Xia, Ying; Long, Jia-Yi; Shen, Meng-Yuan; Dong, Na; Guo, Hong-Li; Hu, Ya-Hui; Lu, Xiao-Peng; Ding, Xuan-Sheng; Chen, Feng; Qiu, Jin-Chun (Frontiers in Pharmacology, 2021)
Background: Valproic acid (VPA) is a widely used antiseizure medication and its dosing needs to be individualized through therapeutic drug monitoring (TDM) to avoid or prevent toxicity. Currently, immune-enzymatic assays such as Enzyme Multiplied Immunoassay Technique (EMIT), and Liquid Chromatography (LC)-based techniques, particularly coupled to Electrospray Ionization Tandem Mass Spectrometry (LC–ESI-MS/MS), resulting a potential lack of concordance between laboratories. Methods: In this study, plasma VPA concentrations were determined for 711 pediatric patients with epilepsy by a routine EMIT assay and by a validated in-house LC-ESI-MS/MS method on the same group of samples, aimed to address the aforementioned concern. Consistency between two methods was evaluated using linear regression and Bland-Altman analysis. Results: A significant correlation between two methods was obtained with a regression equation described as following [EMIT] = 1.214 × [LC-ESI-MS/MS] + 3.054, (r2 = 0.9281). Bland-Altman plot showed a mean bias of 14.5 μg/mL (95% confidence interval (CI): [-0.2, 29.2]) and a mean increase of 27.8% (95% CI: [3.3, 52.4]) measured by EMIT assay more than that measured by LC-ESI-MS/MS method. Conclusions: In conclusion, two methods were closely correlated, but EMIT assay overestimate VPA levels in human plasma compared with LC-ESI-MS/MS method. Considering the observed significant discordance between EMIT and LC-ESI-MS/MS, switching from immunoassays to LC-based techniques for TDM of VPA deserves close attention and further study. Clinicians should be informed when switching the VPA quantitation methods during the clinical practice.